Three new species of Formicaphagus Carriker, 1957 (Phthiraptera, Ischnocera, Philopteridae), parasitic on Thamnophilidae and Conopophagidae (Aves, Passeriformes) - Cicchino, Armando C.; Valim, Michel P. (Zootaxa, 2008)
Three new species of Formicaphagus Carriker, 1957 parasitic on the avian families Thamnophilidae and Conopophagidae are described and illustrated. They and their type hosts are: F. mariae n. sp. from Conopophaga lineata (WiedNeuwied, 1831); F. thamnophili n.sp. from Thamnophilus r. ruficapillus Vieillot, 1816; and F. severus n.sp. from Mackenziaena severa (Lichtenstein, 1823). These chewing lice are the first lice described from these host species. These new species are distinguished from the previously described 11 species chiefly by having postspiracular setae from tergite III (from II in some individuals of the former species), the shape of the head and dorsal anterior plate, chaetotaxy and body measurements.